Systemic lupus erythematosus and Hashimoto's thyroiditis in a female patient.Case presentation - Diana Esperanza Monet Alvarez; Angel Miguel Aguiar Gonzalez; Julia Tamara Álvarez Cortes; Virgen Yaneisi Gross Ochoa (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: Autoimmune diseases are chronic, rare conditions based on immunocomplex deposition, which cause a progressive inflammatory process. The association between two or more of these diseases constitutes rare cases. Hashimoto's thyroiditis is an endocrine disease of autoimmune origin that can sometimes coexist with rheumatic autoimmune diseases, including rheumatoid arthritis and systemic lupus erythematosus. Case Presentation: we present the case of a female patient with a history of bronchial asthma since birth and Hashimoto's thyroiditis (TSH: 100 IU/ml and A-TPO: 478.8 IU/ml) since January 2019, who presents with amenorrhea and one month after treatment with levothyroxine (125 mg daily) is diagnosed with mitral prolapse without organic repercussions so far. She presents joint disorders (pain, calcifications, hypertrophy, synovial fluid effusion), renal disorders (hematuria, proteinuria and leukocyte casts), malar erythema and arterial hypertension due to renal damage. She was diagnosed with systemic lupus erythematosus and treatment with prednisone 10 mg daily (2 tablets of 5mg) and chloroquine 1 tablet daily was decided. Conclusions: this case is interesting because it demonstrates the need for knowledge of autoimmune diseases, their symptomatology and adequate treatment, in order not to confuse the disease with other nosological entities and to be able to make an adequate diagnosis at an early stage, since autoimmune processes can cause severe symptoms if they are not diagnosed and treated in a timely manner, so the clinical method, based on an adequate interrogation and an exhaustive physical examination, is of vital importance.